2018
DOI: 10.20944/preprints201811.0397.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Food Parenting Practices Among Parents with Overweight and Obesity: A Systematic Review

Abstract: Given the links between parental obesity and eating psychopathology in their children, it is important to understand the mechanisms via which unhealthy relationships with eating are passed from parents to children. The aim was to review research focusing on food-related parenting practices (FPPs) used by parents with overweight/obesity. Web of Science, PubMed and PsycINFO were searched. Twenty studies were included in the review. Single studies suggest differences between parents with healthy-weight vs overwei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…These results do suggest however that some maternal exposure(s) that are correlated with the maternal BMI PRS have a causal effect on offspring child/adolescent adiposity, although our analyses are unable to distinguish whether this is a pre or postnatal effect. Plausible mechanisms include intrauterine effects such as fetal overnutrition (1) and postnatal effects such as maternal influence on offspring eating behaviour (66), but other mechanisms have been hypothesised, including periconceptional effects (such as altered oocyte structure or function ( 3)). In linear regression analyses we found moderate to strong evidence for associations between the maternal non-transmitted allele BMI PRS and offspring adolescent adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…These results do suggest however that some maternal exposure(s) that are correlated with the maternal BMI PRS have a causal effect on offspring child/adolescent adiposity, although our analyses are unable to distinguish whether this is a pre or postnatal effect. Plausible mechanisms include intrauterine effects such as fetal overnutrition (1) and postnatal effects such as maternal influence on offspring eating behaviour (66), but other mechanisms have been hypothesised, including periconceptional effects (such as altered oocyte structure or function ( 3)). In linear regression analyses we found moderate to strong evidence for associations between the maternal non-transmitted allele BMI PRS and offspring adolescent adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents with overweight or obese parents are more likely to become overweight themselves [ 65 , 66 , 67 ]. Moreover, parents with higher BMI themselves tend to use different (i.e., unhealthier) FPPs than parents with a healthy weight [ 68 ], and might particularly do so in response to stress [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown a strong correlation between parental food preferences and their child’s food preferences, particularly with fruits, vegetables, sweetened beverages, and meats (Galloway et al, 2006; Yavorsky et al, 2015). Food parenting practices (FPPs) are defined as active techniques or behaviors used by parents to influence a child’s food intake (Patel et al, 2018). FPPs have been found to be one of the environmental factors associated with the development of overweight and obesity in childhood and encompass the behaviors used by parents to influence their child’s behaviors, attitudes, or beliefs around food and eating.…”
Section: Introductionmentioning
confidence: 99%